New occurrences of mollusks from the Santa Marta and Snow Hill Island (Gamma Member) formations, Upper Cretaceous, James Ross Island, Antarctic Peninsula (Terr@ Plural, 2021)
Although the fossil record from Antarctica is increasing continuously, there is still a great lack of knowledge regarding the past biodiversity of this continent. Here we present the first occurrences of the ammonoid Pseudophyllites? cf. latus in the Santa Marta Formation (Santonian-early Campanian) and the scaphopod Laevidentallium? sp. (Laevidentallidae) in the Gamma Member (late Campanian) of the Snow Hill Island Formation (late Campanian - early Maastrichtian). The presence of Laevidentalliidae in the Gamma Member characterizes the oldest occurrence of this family in Antarctica and it is apparently another taxon that originated in this continent and later migrated to lower latitudes.
Keywords: Ammonoidea; Scaphopoda; Santonian-Campanian; Larsen Basin; Antarctica